30.7k views
1 vote
What is (-12x+6)+(4x-12)​

User Spyryto
by
4.9k points

2 Answers

4 votes

Final Result :

-2 • (4x + 3)

Processing ends successfully

User Petko Kamenov
by
4.5k points
1 vote

Answer:


x=-(3)/(4)

Explanation:

Given Equation:


(-12x+6)+(4x-12)\\

Taking the standard form of the equation to solve for 'x':


(-12x+6)+(4x-12)=0

Opening the brackets:


-12x+6+4x-12=0

Adding the like terms:


-8x+6-12=0\\\\-8x-6=0

Adding '6' both sides:


-8x=6

Dividing by '-8' both sides:


x=(6)/(-8) \\\\x=-(3)/(4)

User Yanhong
by
5.2k points